2010
DOI: 10.1179/136217110x12720264008277
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic stirring on grain structure refinement: Part 1 – Autogenous nickel alloy welds

Abstract: The objectives of this work were to characterise and understand the effects of circular magnetic arc deflection (arc stirring) on grain structure refinement of gas tungsten arc weld beads made in Inconel 690 substrates. Welds were made at various arc stirring frequencies (1?5-50 Hz), and microstructures were analysed using optical and electron backscattered diffraction microscopy. Optimum refinement of grain size occurred at a stirring frequency of ,7 Hz. Analysis of computational fluid flow, heat transfer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Analysis of autogenous weld results showed that circular scanning frequencies of 2, 4 and 8 Hz, produced welds with a microstructure consisting of a mixture of columnar and equiaxed grains, but at a frequency of 7 Hz, a microstructure consisting of only small, equiaxed grains was observed. 17 The effectiveness of 7 Hz scanning for autogenous weld grain refinement is vividly illustrated in the micrograph displayed in Fig. 2, which shows the re-emergence of the columnar grains (marked by arrows) when circular scanning at 7 Hz frequency was turned off.…”
Section: Microstructure Analysesmentioning
confidence: 96%
“…Analysis of autogenous weld results showed that circular scanning frequencies of 2, 4 and 8 Hz, produced welds with a microstructure consisting of a mixture of columnar and equiaxed grains, but at a frequency of 7 Hz, a microstructure consisting of only small, equiaxed grains was observed. 17 The effectiveness of 7 Hz scanning for autogenous weld grain refinement is vividly illustrated in the micrograph displayed in Fig. 2, which shows the re-emergence of the columnar grains (marked by arrows) when circular scanning at 7 Hz frequency was turned off.…”
Section: Microstructure Analysesmentioning
confidence: 96%
“…35 These models will be able to predict any tendency for defect formation as well as microstructural heterogeneity. 113 In the next step, some of the sacrifi cial samples that are produced together with the component are characterized nondestructively with ultrasonics, 114 computer-aided tomography using x-ray or neutron tomography, 36 as well as residual stress distribution. 115 The next step in qualifi cation is the data set that can be used for component qualifi cation.…”
Section: Current Challenges and Qualifi Cation Issuesmentioning
confidence: 99%
“…[9][10][11][12][13][14]. Entretanto, a oscilação magnética sincronizada com o processo de soldagem TIG não parace ter sido ainda explorada.…”
Section: Soldagem Tig Com Oscilação Magnética Sincronizadaunclassified